PERSONAL PERSON TAXPAYER COMPLIANCE REVIEWED FROM QUALITY OF SERVICE, TAX AWARENESS, AND THE MOTIVATION TO PAY TAXES (Study at Pratama Klaten Tax Service Office) - Agnes Dara Ardisari; Istiatin Istiatin; Sudarwati Sudarwati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The objectives of this study are: (1) To determine the effect of service quality, tax awareness, motivation to pay taxes simultaneously on individual taxpayer compliance at Klaten Primary Tax Office, (2) To determine the effect of service quality on individual taxpayer compliance at Klaten Primary Tax Office, (3) To determine the effect of tax awareness on the compliance of individual taxpayers at Klaten Primary Tax Office, and (4) To determine the influence of motivation to pay taxes on individual taxpayer compliance at Klaten Primary Tax Office. Type of quantitative research. The population is an individual taxpayer at Klaten Primary Tax Office. Researchers took 100 taxpayers as samples. The sampling technique used in this study was purposive sampling. The data collection technique used a questionnaire. The data analysis technique is multiple linear regression. The results showed that (1) service quality variables, tax awareness, and motivation to pay taxes simultaneously have an effect on taxpayer compliance at Klaten Primary Tax Office, (2) the quality of service has an effect on the compliance of taxpayers at Klaten Primary Tax Office, (3) awareness of taxation affects the compliance of taxpayers at Klaten Primary Tax Office, and (4) motivation to pay taxes affects the compliance of taxpayers at Klaten Primary Tax Office Keywords: service quality, awareness, motivation, compliance,